Switchable unipolar-barrier van der Waals heterostructures with natural anisotropy for full linear polarimetry detection - Deng, Wenjie (2022)
Polarization-resolved photodetection in a compact footprint is of great interest for ultraminiaturized polarimeters to be used in a wide range of applications. However, probing the states of polarization (SOP) in materials with natural anisotropy are usually weak, limited by the material's natural dichroism or diattenuation. Here, a twisted unipolar-barrier van der Waals heterostructure (vdWH) to construct a bias-switchable polarization detection for retrieval of full SOP (from 0 to 180°) for linear polarized incident light is reported. As a demonstration example, this study realizes the concept in a b-AsP/WS2 /b-AsP vdWH relying on the natural anisotropic properties of the materials without using additional plasmonic/metasurface nanostructures to realize linear polarimetry in the mid-infrared range. Polarimetric imaging is further demonstrated with the developed linear polarimetry by directly displaying the Jones-vector-described SOP distribution of certain target object. This method, with the capabilities of detecting full linear SOP, is promising for the next-generation on-chip miniaturized polarimeters.